(3WHbGJ GdNhGU Cgd GdUOb hGdENdGUs - (3GdRHjOj , CMeO Hf CMeO Hf YHO GddWja GdTQLj, TgGH GdOjf,J (B893 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdeJaVd HLRjd GdehGgH hGdYWG s
(3BNQgG (B:s
(3gPG BNQ eG JjSQ LeYg ef PcQ gDdGA GdSGOI hGdMeO ddg ChdkG hBNQkG hGdMeO ddg GdPi HfYeJg JJe GdUGdMGJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3Ydi MhGTjgG HYV GdJYdjbGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B91 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B150s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHg GdTjN CMeO Hf eMeO GdSGdei GdNGUg HRHjO s
Keywords: (3GdJUha hGdBOGH GdTQYjIs